NEXUS Gains Talk 13: Managed Aquifer Recharge in the Ganges Basin - Pavelic, Paul; Sharma, Navneet; Alam, Faiz; Angou, Gayathri; Ross, Andrew (CGIAR System Organization, 2023)
Underground Transfer of Floods for Irrigation (UTFI) is a form of managed aquifer recharge that helps boost groundwater storage in depleted aquifers, while reducing seasonal flooding and building resilience to agricultural droughts. UTFI has been successfully piloted at the community level in the Ganges Basin and contributed towards district-level scaling through various Government of India programs. Although field experiences have been focused within the Ganges, the opportunities at the global scale have also been examined. This NEXUS Gains webinar provides an overview of UTFI concepts and evidence, and introduces the work underway to examine the barriers to wider implementation.